A New Way to Beat Intestinal Pathogens. Issue 3 (March 2017) - Detweiler, Corrella S.
Abstract : In the gastrointestinal tract, the tug of war for iron may provide a new way to vaccinate. Recent work shows that immunizing mice with siderophores (small molecules that microbes produce to capture iron) foils pathogen colonization and may instead allow a commensal to expand.